A photoheterotrophic bacterium from Iceland has adapted its photosynthetic machinery to the long days of polar summer - Tomasch, Jürgen; Kopejtka, Karel; Bílý, Tomáš; Gardiner, Alastair T; Gardian, Zdenko; Shivaramu, Sahana; Koblížek, Michal; Kaftan, David (mSystems, 2024)
During their long evolution, anoxygenic phototrophic bacteria have inhabited a wide variety of natural habitats and developed specific strategies to cope with the challenges of any particular environment. Expression, assembly, and safe operation of the photosynthetic apparatus must be regulated to prevent reactive oxygen species generation under illumination in the presence of oxygen. Here, we report on the photoheterotrophic Sediminicoccus sp. strain KRV36, which was isolated from a cold stream in north-western Iceland, 30 km south of the Arctic Circle. In contrast to most aerobic anoxygenic phototrophs, which stop pigment synthesis when illuminated, strain KRV36 maintained its bacteriochlorophyll synthesis even under continuous light. Its cells also contained between 100 and 180 chromatophores, each accommodating photosynthetic complexes that exhibit an unusually large carotenoid absorption spectrum. The expression of photosynthesis genes in dark-adapted cells was transiently downregulated in the first 2 hours exposed to light but recovered to the initial level within 24 hours. An excess of membrane-bound carotenoids as well as high, constitutive expression of oxidative stress response genes provided the required potential for scavenging reactive oxygen species, safeguarding bacteriochlorophyll synthesis and photosystem assembly. The unique cellular architecture and an unusual gene expression pattern represent a specific adaptation that allows the maintenance of anoxygenic phototrophy under arctic conditions characterized by long summer days with relatively low irradiance.IMPORTANCEThe photoheterotrophic bacterium Sediminicoccus sp. KRV36 was isolated from a cold stream in Iceland. It expresses its photosynthesis genes, synthesizes bacteriochlorophyll, and assembles functional photosynthetic complexes under continuous light in the presence of oxygen. Unraveling the molecular basis of this ability, which is exceptional among aerobic anoxygenic phototrophic species, will help to understand the evolution of bacterial photosynthesis in response to changing environmental conditions. It might also open new possibilities for genetic engineering of biotechnologically relevant phototrophs, with the aim of increasing photosynthetic activity and their tolerance to reactive oxygen species.
Keywords: Photosynthesis; reaktivní formy kyslíku; gene expression; photosynthesis; Island; Sediminicoccus; AAP; Photosynthetic Reaction Center Complex Proteins; Reactive Oxygen Species; Bacteriochlorophylls; bakteriochlorofyly; light adaptation; Proteobacteria; Oxygen; kyslík; fotosyntetická reakční centra (proteinové komplexy); Iceland; Bacteria; fotosyntéza